Exosomal PKM2 from AML cells reprograms endothelial metabolism to promote angiogenesis and chemoresistance - Xiaoting Wang; Ruolan You; Wenqi Fang; Lixia Kang; Danni Cai; Diyu Hou; Jingru Liu; Shuxia Zhang; Huifang Huang (Functional & Integrative Genomics, 2026)

A meta analysis of N2O emission characteristics and influencing factors in facultative composting and an estimation of emissions in China - Kaishu Luo; Ruolan Tang; Yan Liu; Yaru Shao; Guoxue Li; Jing Yuan (Environmental Research, 2026)

Two-phase removal kinetics of antimicrobial resistance in collaborative composting: Thermophilic enhancement and rebound suppression - Ruonan Ma; Xuyan Li; Ruolan Tang; Yan Liu; Jiani Wang; Guoxue Li; Si Li; Shenzhong Tian; Tao Jiang; Jiali Chang; Jing Yuan (Bioresource Technology, 2026)

Spatiotemporal dynamics and spatial attribution of water conservation under land use/cover changes and the SSP2–4.5 medium-forcing scenario in the northern slope of the Tianshan Mountains - Hongjie Jia; Qin Han; Yingchao Ji; Dong Liu; Ruolan Chen; Jiangyue Li; Haoyang Du (Regional Environmental Change, 2026)

A comparative study of methods for quantifying sand-sized sediment grain textural parameters - Xiaotian Shen; Xing Jian; Wei Zhang; Ruolan Liao; Dongming Hong; Chao Li; Shaohua Zhao; James T. Liu; Yuan-Pin Chang (Sedimentary Geology, 2026)

The impact of the construction of national key ecological function zones on county-level ecological resilience - Chao Chen; Ruolan Yuan; Yang Liu; Feng Ye; Wenmei Liao (Environment, Development and Sustainability, 2026)

Characterization and encapsulation properties of pectic polysaccharides derived from Choerospondias axillaris fruit - Hao Liu; Ruolan Du; Hongxiang Li; Wenbo Zhao; Liang Leng; Jun Lu; Haiqiang Zhang; Sanyin Zhang (Carbohydrate Polymers, 2026)

Pyrolysis characteristics and kinetics of typical Chinese herbal medicine residues - Jigang Zhang; Ruolan Cao; Minghua You; Yang Liu; Kuihua Han (Biomass and Bioenergy, 2026)

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

RSAND: A Fine-Grained Dataset and Benchmark for AtoN Detection in River–Sea Intermodal and Complex Estuarine Environments - Qi Chen; Mingyang Pan; Zongying Liu; Ruolan Zhang; Fei Yan; Xiaofeng Pan; Yang Zhang; Chao Li (Journal of Marine Science and Engineering, 2026)
Robust visual perception of Aids to Navigation (AtoN) is essential for Maritime Autonomous Surface Ships (MASS) operating in restricted navigational waters, where estuarine clutter, fog, glare, and dense traffic can severely degrade detection reliability. Existing maritime vision datasets largely emphasize open-sea targets or coarse AtoN categories, leaving a granularity gap for IALA-compliant fine-grained understanding in river–sea transition and port-approach channels. The River–Sea AtoN Navigation Dataset (RSAND) is introduced, a large-scale benchmark collected along the Yangtze River Deepwater Channel from inland corridors to open estuarine waters. RSAND contains 39,926 images with expert-verified bounding-box annotations and a hierarchical taxonomy that jointly captures AtoN location, shape, and functional semantics across 29 categories. To support both realistic long-tailed evaluation and standardized model comparison, two protocols are provided: RSAND-Full (29 categories) and RSAND-Balanced (10 critical categories). All quantitative benchmarking results in this paper are reported on RSAND-Balanced, while RSAND-Full is released for future large-scale long-tailed robustness studies. Benchmarking experiments on 14 state-of-the-art detectors demonstrate that YOLOv12x achieves superior performance with an mAP50-95 of 80.7%, significantly outperforming previous baselines. However, the analysis reveals persistent challenges in detecting small, distant targets and distinguishing visually similar functional markers. RSAND and the accompanying evaluation toolkit are released to facilitate reproducible research toward safer and smarter marine and coastal navigation.

Functional differentiation of Sojae semen Praeparatum: A multi-omics analysis of the effects of Artemisia annua and Mori folium on composition, microorganisms, and functional characteristics - Yingying Cheng; Bing Wang; Qiaoling Ma; Min Sun; Xintong Wang; Ruolan Wang; Hongping Chen; Lin Chen; Youping Liu; Fu Wang; Chuan Zheng; Yuan Hu (Food Research International, 2025)

Atmospheric and room-temperature plasma mutagenesis enhances the tolerance of Arthrospira platensis to photoinhibition and high-CO2 levels - Ruolan Yuan; Chunli Yu; Rui Xu; Jin Liu; Lina Zhou; Shengxi Shao; Jun Qian; Jingjing Li; Peilun Xu; Wenguang Zhou (Chemical Engineering Journal, 2025)

Defect-engineered Z-scheme BiOBr/TiO2 heterojunctions with interfacial potential wells for selective CO2 photoreduction - Shijie Liu; Ruolan Zhao; Yachao Xu; Maoxiang Li; Zihan Ma; Xin Chang; Ying Wang; Mingyi Zhang (Chemical Engineering Journal, 2025)

Optimizing organic waste co-composting: Component ratio thresholds for dual enhancement of maturity and gaseous emission reduction - Ruonan Ma; Ruolan Tang; Guannan Zheng; Jiani Wang; Zhongliang Cui; Yan Liu; Guoxue Li; Fanqiao Meng; Jing Yuan (Journal of Environmental Chemical Engineering, 2025)

Response of maturity, humification, and gaseous emissions to initial moisture content in collaborative composting of multiple organic solid wastes - Xuyan Li; Jiacong Lin; Ruolan Tang; Yan Liu; Jiani Wang; Guoxue Li; Jing Yuan; Ruonan Ma (Journal of Environmental Chemical Engineering, 2025)

Therapeutic potential of Angelica sinensis derivatized carbon dots in ameliorating chemotherapy-induced anemia - Ruolan Kong; Yujiao Yuan; Jiaxing Liu; Kai Cheng; Yifan Zhang; Xiwen Zhang; Peng Zou; Yan Huang; Jinyu Ma; Chenxin He; Hui Kong; Yan Zhao; et al. (Journal of Molecular Histology, 2025)

Tidal channel morphology controls on water exchange and sedimentation Patterns: Implications for sustainable reclamation design in semi-enclosed lagoons - Ruolan Yu; Chen Zhang; Zixuan Zhu; Yinzhu Liu (Marine Environmental Research, 2025)

Black phosphorus-doped Janus structured electrospun fibrous membrane with antibacterial properties for wound healing - Ruolan Du; Xinyu Li; Wenbo Wu; Jingxin Zhou; Zhiwei Liu; Yuehua Wang; Tifeng Jiao (Chemical Engineering Journal, 2025)

A reversible fluorescence probe enables bioimaging and toxicity evaluation of lithium ion in living human cells - Cheng Gong; Peiming Zhang; Ya Liu; Ruolan Chen; Kai Huang; Weizhun Yang; Lirong Gao; Ming Xu; Xuezhi Yang; Yin Liu; Qian Liu; Bing Yan; et al. (Journal of Hazardous Materials, 2025)

Optimization of sludge retention time for rapid start-up and stable operation of high-rate partial nitritation in a continuous flow reactor treating municipal wastewater - Ruolan Wen; Min Ye; Yanxu Liu; Chihao Lin; Yu-You Li; Jianyong Liu (Journal of Environmental Management, 2025)

Examination of green roofs' cooling effects in a big city based on multi-source remote sensing data: An example from central Xi’an, China - Xiya Yan; Jianhong Liu; Wei Zhang; Ziqi Wang; Ruolan Jia; Lei Wang; Nan Liu; Yu Zhu (Sustainable Cities and Society, 2025)

Bioremediation potential of sulfadiazine-degrading bacteria: Impacts on ryegrass growth and soil functionality - Minghao Yin; Ping Li; Chengzhuang Chen; Ruolan Jia; Banghua Xia; Yiwei Liu; Aiqiu Liu; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Plant secretions and volatiles contribute to the evolution of bacterial antibiotic resistance in soil-crop system - Houyu Li; Qifan Yang; Wei Liu; Ruolan Li; Dandan Zhang; Guilong Zhang; Yan Xu (Journal of Environmental Sciences, 2025)

Iron-modified biochar enhanced nitrogen retention during composting:bridging chemisorption and microbiome modulation - Ruolan Tang; Sheng Yao; Yan Liu; Tianyu Ren; Jingyuan Ma; Xiaoyan Gong; Guoxue Li; Ruonan Ma; Jing Yuan (Chemical Engineering Journal, 2025)

Mapping cropland use changes in the Guanzhong Plain of China based on a two-level classification framework - Wei Zhang; Jianhong Liu; Ruolan Jia; Xi Wang; Xiya Yan; Ziqi Wang; Jing Wang; Wei Li; Peijun Sun (International Journal of Remote Sensing, 2025)

A chemically enhanced primary treatment and anammox-based process for sustainable municipal wastewater treatment: The advantage and application prospects - Ruolan Wen; Jiayuan Deng; Huan Yang; Yu-You Li; Hui Cheng; Jianyong Liu (Journal of Environmental Management, 2025)

Gender differences in commuting travel mode choices among young adults: A spatial heterogeneity perspective - Yang Liu; Ruolan Shen; Mingwei He; Xuefeng Li; Zhuangbin Shi (Journal of Transport Geography, 2025)

Identification and Removal of Light Pollution in Maritime Night-Time Images Based on Spatial Frequency Blocks - Hui Sun; Jingyang Wang; Mingyang Pan; Zongying Liu; Shaoxi Li; Ruolan Zhang; Yang Wei (Journal of Marine Science and Engineering, 2025)
The safety of ships during nighttime navigation has always been a major concern. With the widespread application of technologies such as intelligent recognition, intelligent detection, and unmanned ship navigation at night, nighttime maritime light pollution has significantly affected the effectiveness of these intelligent technologies and navigation safety. Therefore, effectively eliminating nighttime maritime light pollution has become an urgent challenge that needs to be addressed. This paper presents a model based on spatial frequency blocks (SFBs) to solve the problem of light pollution in nighttime sea images. The model includes ResNet-50, an encoder, a decoder, and a discriminator. To enable the model to better remove the influence of light pollution, this study designs a method of first detecting the light pollution area and then removing it. It extracts image information from the space–frequency domain to help eliminate light pollution and retain more image information. The experimental results show that on the nighttime light pollution dataset, the Peak Signal-to-Noise Ratio (PSNR) of the model is improved to 24.91 compared to the current state-of-the-art image restoration model, while the Frechet inception distance (FID) is reduced to 64.85. At the same time, in the real night environment, the model can better remove light pollution to recover the original nighttime information. It has excellent performance and provides a certain reference value for advancing the safety of nighttime maritime navigation.

Correlation analysis and modeling application from objective indicators to subjective evaluation of scented tea: A case study of rose tea - Ruolan Song; Meng Shen; Yanran Wang; Youyi Sun; Jiamu Ma; Qingyue Deng; Xueyang Ren; Xianxian Li; Yuan Zheng; Yingyu He; Feng Zhang; Mingxia Li; et al. (Food Chemistry, 2025)

Effects of single or combined exposure to tralopyril and ocean acidification on energy metabolism response and sex development in Pacific oysters (Crassostrea gigas) - Ping Li; Minghao Yin; Xu Wang; Ruolan Jia; Chengzhaung Chen; Bin Liu; Yiwei Liu; Bianhao Zeng; Tengzhou Li; Ling Liu; Hong-Jun Song; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Phosphate, magnesium containing additives and biochar regulate compost maturity and synergistically reduce odor emission in chicken manure composting: Role of physicochemical, bacterial and fungal dynamics - Yan Liu; Ruonan Ma; Ruolan Tang; Guannan Zheng; Guoxue Li; Jie Yin; Jing Yuan (Journal of Environmental Management, 2024)

Ground visibility prediction using tree-based and random-forest machine learning algorithm: Comparative study based on atmospheric pollution and atmospheric boundary layer data - Fuzeng Wang; Ruolan Liu; Hao Yan; Duanyang Liu; Lin Han; Shujie Yuan (Atmospheric Pollution Research, 2024)

Dicyandiamide addition delay nitrous oxide emission and shift its production pathway from denitrification to incomplete nitrification in maturation phase of composting - Yan Liu; Ruolan Tang; Guoliang Liu; Guoxue Li; Jiani Wang; Yu Cai; Yilin Kong; Jing Yuan (Chemical Engineering Journal, 2024)

Rapid Joule heating-induced welding of silicon and graphene for enhanced lithium-ion battery anodes - Fan Yang; Pengcheng Deng; Hang He; Ruolan Hong; Kun Xiang; Yuan Cao; Beibei Yu; Zeman Xie; Jiming Lu; Zikang Liu; Danish Khan; David Harbottle; et al. (Chemical Engineering Journal, 2024)

Injectable exosome-loaded quaternized chitosan/oxidized sodium alginate hydrogel with self-healing, bioadhesive, and antibacterial properties for treating combined radiation-wound injury - Guanqun Peng; Jia Hu; Jinnan Guo; Jiahui Dong; Yuanyuan Zhao; Tong Ye; Fengjun Xiao; Zhiyun Meng; Hui Gan; Ruolan Gu; Peng Han; Wenzhong Sun; et al. (Chemical Engineering Journal, 2024)

Rapid and highly sensitive colorimetric LAMP assay and integrated device for visual detection of monkeypox virus - Yadan Peng; Ruolan Hu; Shuang Xue; Yugan He; Lili Tian; Zehan Pang; Yile He; Yuqi Dong; Yinghan Shi; Shuqi Wang; Bixia Hong; Ke Liu; et al. (Analytica Chimica Acta, 2024)

Ferroptosis is involved in trophoblast cells cytotoxicity induced by black phosphorus nanoparticles - Ruolan You; Yaming Mu; Jiaqi Zhou; Chunying Wang; Zhenya Fang; Yu Liu; Shiyu Liu; Qingfeng Zhai; Changqing Zhang (Toxicology, 2024)

Acceleration of the charge transfer rate for efficient photocatalytic hydrogen production via adjusting modulator and introducing electronic bridge dual strategies - Xingyan Liu; Haibo Zhou; Ruolan Li; Maosen Xu; Chenghua Zhang; Zhengsijia Wu; Youzhou He; Xu Zou; Min Fu; Siping Wei (Fuel, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Plasma-Free Blood as a Potential Alternative to Whole Blood for Transcriptomic Analysis - Qingwang Chen; Xiaorou Guo; Haiyan Wang; Shanyue Sun; He Jiang; Peipei Zhang; Erfei Shang; Ruolan Zhang; Zehui Cao; Quanne Niu; Chao Zhang; Yaqing Liu; et al. (Phenomics, 2024)
RNA sequencing (RNAseq) technology has become increasingly important in precision medicine and clinical diagnostics, and emerged as a powerful tool for identifying protein-coding genes, performing differential gene analysis, and inferring immune cell composition. Human peripheral blood samples are widely used for RNAseq, providing valuable insights into individual biomolecular information. Blood samples can be classified as whole blood (WB), plasma, serum, and remaining sediment samples, including plasma-free blood (PFB) and serum-free blood (SFB) samples that are generally considered less useful byproducts during the processes of plasma and serum separation, respectively. However, the feasibility of using PFB and SFB samples for transcriptome analysis remains unclear. In this study, we aimed to assess the suitability of employing PFB or SFB samples as an alternative RNA source in transcriptomic analysis. We performed a comparative analysis of WB, PFB, and SFB samples for different applications. Our results revealed that PFB samples exhibit greater similarity to WB samples than SFB samples in terms of protein-coding gene expression patterns, detection of differentially expressed genes, and immunological characterizations, suggesting that PFB can serve as a viable alternative to WB for transcriptomic analysis. Our study contributes to the optimization of blood sample utilization and the advancement of precision medicine research.

Ocean acidification alters shellfish-algae nutritional value and delivery - Ruolan Jia; Minghao Yin; Xue Feng; Chengzhuang Chen; Chunfeng Qu; Ling Liu; Ping Li; Zhi-Hua Li (Science of The Total Environment, 2024)

Semi-dynamic spatial–temporal graph neural network for traffic state prediction in waterways - Le Li; Mingyang Pan; Zongying Liu; Hui Sun; Ruolan Zhang (Ocean Engineering, 2024)

Rice bran peptide with α-glucosidase inhibition activity: Preparation, evaluation and molecular mechanism - Weiwei Liu; Ruolan Ma; Gengjie Cui; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Journal of Cereal Science, 2024)

Chemometrics-based investigation of non-volatiles/volatiles flavor of tencha (Camellia sinensis cv. Yabukita, Longjing 43 and Baiye 1) - Qiuwen Yu; Chuangsheng Huang; Ruolan Zhu; Debiao Lu; Liping Liu; Jianhong Lai; Xinyao Zhong; Jueshan Guan; Senjie Zhou; Yilin Tong; Zipei Wang; Ping Chen; et al. (Food Research International, 2023)

Downregulation of ITGA5 inhibits lymphangiogenesis and cell migration and invasion in male laryngeal squamous cell carcinoma - Xiaoting Wang; Jun Huang; Ruolan You; Diyu Hou; Jingru Liu; Long Wu; Meihong Yao; Fuwen Yang; Huifang Huang (Protoplasma, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

A global meta-analysis of greenhouse gas emissions and carbon and nitrogen losses during livestock manure composting: Influencing factors and mitigation strategies - Yan Liu; Ruolan Tang; Liqiong Li; Guannan Zheng; Jiani Wang; Guoying Wang; Ziyang Bao; Ziming Yin; Guoxue Li; Jing Yuan (Science of The Total Environment, 2023)

Effect of soil water–phosphorus coupling on the photosynthetic capacity of Robinia pseudoacacia L. seedlings in semi-arid areas of the Loess Plateau, China - Minxia Liu; Chunliang Yang; Ruolan Mu (Environmental Monitoring and Assessment, 2023)

Preparation and application of cinnamon-Litsea cubeba compound essential oil microcapsules for peanut kernel postharvest storage - Haoxin Lv; Shanshan Huo; Lingli Zhao; Hanxiao Zhang; Yijun Liu; Shichang Liu; Akio Tani; Ruolan Wang (Food Chemistry, 2023)

Clarifying the effect of gut microbiota on allergic conjunctivitis risk is instrumental for predictive, preventive, and personalized medicine: a Mendelian randomization analysis - Kangcheng Liu; Yingjun Cai; Kun Song; Ruolan Yuan; Jing Zou (EPMA Journal, 2023)

Shellfish-algal systems as important components of fisheries carbon sinks: Their contribution and response to climate change - Ruolan Jia; Ping Li; Chengzhuang Chen; Ling Liu; Zhi-Hua Li (Environmental Research, 2023)

Impact of battery electric vehicles on ventilation design for road tunnels: A review - Xu Wang; Mingnian Wang; Ruolan Jiang; Jiani Xu; Bingtian Li; Xiao Wang; Mingyu Lei; Pengfei Su; Chaopeng Liu; Qianru Yang; Jianle Yu (Tunnelling and Underground Space Technology, 2023)

Effects of radon exposure on gut microbiota and its metabolites short-chain fatty acids in mice - Huimeng Liu; Meiyu Wang; Guangrui Chen; Huiyu Zhou; Jiahui Dong; Lei Yang; Tong Li; Zhiyun Meng; Ruolan Gu; Hui Gan; Zhuona Wu; Shuchen Liu; et al. (Toxicology, 2023)

Boosting the photocatalytic hydrogen evolution and NO removal via synergistic effects of in-situ Pt NPs formation and titanium integration in Zr-Porphyrin MOFs - Ruolan Li; Zongqian Wu; Ya Chen; Xingyan Liu; Weiwei Guo; Yumin Huang; Min Fu; Youzhou He (Fuel, 2023)

Effect of moisture content, aeration rate, and C/N on maturity and gaseous emissions during kitchen waste rapid composting - Ruolan Tang; Yan Liu; Ruonan Ma; Lanxia Zhang; Yanming Li; Guoxue Li; Dingmei Wang; Jiacong Lin; Qinfen Li; Jing Yuan (Journal of Environmental Management, 2023)

Evaluation and Hydrological Application of CMADS Reanalysis Precipitation Data against Four Satellite Precipitation Products in the Upper Huaihe River Basin, China - Shanhu Jiang; Ruolan Liu; Liliang Ren; Menghao Wang; Junchao Shi; Feng Zhong; Zheng Duan (Journal of Meteorological Research, 2020)

Identification and functional characterization of a p-coumaroyl CoA 2′-hydroxylase involved in the biosynthesis of coumarin skeleton from Peucedanum praeruptorum Dunn - Ruolan Yao; Yucheng Zhao; Tingting Liu; Chuanlong Huang; Sheng Xu; Ziwei Sui; Jun Luo; Lingyi Kong (Plant Molecular Biology, 2017)